Pengaruh Kompetensi SDM, Pengembangan Karir Dan Komitmen Karyawan Terhadap Kinerja Karyawan Di Balai Penelitian Tanaman Aneka Kacang Dan Umbi (Balitkabi) Malang - Dewa Putra Andreana; Dianawati Suryaningtyas; Andi Nu Graha (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2019)
This research aims to determine the influence of human resources competence, career development and employee commitment to the performance of employees in the research hall of various nuts and tuber (Balitkabi) Malang. This type of research is quantitative research. The population in the study was all employees of the existing Balitkabi Malang. The samples used in this study were officers in Balikabi Malang. The data analysis techniques used in this study are multiple linear regression analyses. The results of this study showed that the variable of HR competency, Career development and employee commitment simultaneously positively influence the performance of employees at Balitkabi Malang. As well as a parcial HR competency influential insignificant to the employee's performance. While career advancement and employee commitment significantly influence the performance of employees at Balitkabi Malang.